The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4103/ijpc.ijpc_114_19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of psychosocial distress among the palliative care patients in Wardha District of Maharashtra

Abstract: Aim: Palliative Care Outcome Scale (POS) is one of the various tools, available for the evaluation of the effectiveness of palliative services, having 10item multidimensional questionnaire, designed to assess the physical, psychosocial, spiritual, and practical aspects of patients with various sufferings. In this study, we had assessed psychosocial distress among the patients of a palliative care clinic of a rural teaching hospital at Wardha district. Methods: In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Our aim is to increase awareness and understanding of health care providers and the general population through the introduction of palliative care in the educational curriculum in both the medical and dental fields [18][19][20][21] Key results: In proposed cross sectional study having patients of palliative care various sociodemographic variables such as education, occupation, age, socioeconomic status, marital status, various addictions etc will be analysed after the final statistical analysis we will determine-Opinion, belief and severity of various variables of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Our aim is to increase awareness and understanding of health care providers and the general population through the introduction of palliative care in the educational curriculum in both the medical and dental fields [18][19][20][21] Key results: In proposed cross sectional study having patients of palliative care various sociodemographic variables such as education, occupation, age, socioeconomic status, marital status, various addictions etc will be analysed after the final statistical analysis we will determine-Opinion, belief and severity of various variables of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The most common concerns reported by Hindi speaking patients receiving palliative care services were pain, dyspnea, restlessness, bowel obstruction, depression, anxiety, stress, poor quality of life, changes in sleep, appetite, energy, spiritual/religious concerns, family emotional issues, social security, and financial needs. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] A brief review of available tools and literature suggested that concerns raised in the IPOS were holistic and covered all concepts confirming face and content validity.…”
Section: Phase I: Equivalence Settingmentioning
confidence: 99%